Understanding and addressing racial stress and trauma in schools: A pathway toward resistance and healing - Saleem, Farzana T.; Howard, Tyrone C.; Langley, Audra K. (Psychology in the schools, 2022)
Youth of color are disproportionately impacted by stressful and traumatic life events, including race‐based experiences, which are linked to negative consequences. School is a salient context where youth encounter, witness, and process racial stress and trauma (RST). However, RST is often overlooked within general school‐based trauma models. Thus, we propose the School Trauma and Racial Stress (STARS) blueprint, focused on RST across three levels of the school ecology. By building upon and expanding the Substance Abuse and Mental Health Services Administration recommendations regarding trauma‐informed approaches (2014), the STARS blueprint applies a multilevel approach to acknowledging and addressing RST within schools. This integrated framework is a call to action across the school ecology, with the goal to increase recognition of RST within school‐based trauma‐informed approaches and to build racial equity and healing for students of color in K‐12 schools. Practical applications for schools are discussed. Highlights The School Trauma and Racial Stress (STARS) blueprint builds upon core trauma‐informed elements to explicitly acknowledge and address racial stress and trauma within a multilevel school‐wide approach. The framework is a call to action to build and sustain pathways towards resistance, healing, and resilience.